Controlled multi-vinyl monomer homopolymerization through vinyl oligomer combination as a universal approach to hyperbranched architectures - Zhao, Tianyu; Zheng, Yu; Poly, Julien; Wang, Wenxin (Nature communications, 2013)
The three-dimensional structures of hyperbranched materials have made them attractive in many important applications. However, the preparation of hyperbranched materials remains challenging. The hyperbranched materials from addition polymerization have gained attention, but are still confined to only a low level of branching and often low yield. Moreover, the complication of synthesis only allows a few specialized monomers and inimers to be used. Here we report a ‘Vinyl Oligomer Combination’ strategy; a versatile approach that overcomes these difficulties and allows facile synthesis of highly branched polymeric materials from readily available multi-vinyl monomers, which have long been considered as formidable starting materials in addition polymerization. We report the alteration of the growth manner of polymerization by controlling the kinetic chain length, together with the manipulation of chain growth conditions, to achieve veritable hyperbranched materials, which possess nearly 70% branch ratios as well as numerous vinyl functional groups. Hyperbranched polymers have desirable properties as novel materials, and may be synthesized from homopolymerization of multi-vinyl momomers, although this can form insoluble products at low conversions. Here, the authors produce hyperbranched polymers in high yield owing to a kinetic control mechanism.